School Library Management to Develop Students' Interest in Reading in Junior High School: Manajemen Perpustakaan Sekolah untuk Meningkatkan Minat Baca Siswa SMP - Aprianti, Wike; Ibnu Muzakir, Muchammad (Yapilin Press, 2025)
School libraries are essential in supporting teaching and learning activities and increasing students' interest in reading. This study aims to analyse library management at Annakhil Darunnajah 6 Junior High School, Mukomuko, Bengkulu, to foster and develop students' interest in reading. The research methods used include observation, interviews, and documentation. Based on the results of the study, it shows that the management of the school library to foster and develop students' interest in reading at SMP Annakhil Darunnajah 6 includes five stages, including: (1) The library planning stage, which includes the vision, mission, and goals of the library, has been carried out well. (2) The stage of organising the library includes the division of tasks and coordination, which still needs to be improved. (3) The implementation stage of library management consists of borrowing, reading, and literacy services, which are running well. (4) The supervision stage of library management is carried out by the person in charge with direct observation and written reports; and (5) The evaluation stage of library management, which is carried out weekly and monthly by the library team and the principal. Overall, the library management at this school has been running well, but improvements are still needed in coordination and continuous evaluation